2013
DOI: 10.2337/db12-1039
|View full text |Cite
|
Sign up to set email alerts
|

PXR Ablation Alleviates Diet-Induced and Genetic Obesity and Insulin Resistance in Mice

Abstract: The pregnane X receptor (PXR), along with its sister receptor constitutive androstane receptor (CAR), was initially characterized as a xenobiotic receptor that regulates drug metabolism. In this study, we have uncovered an unexpected endobiotic role of PXR in obesity and type 2 diabetes. PXR ablation inhibited high-fat diet (HFD)–induced obesity, hepatic steatosis, and insulin resistance, which were accounted for by increased oxygen consumption, increased mitochondrial β-oxidation, inhibition of hepatic lipoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 39 publications
9
133
2
Order By: Relevance
“…These results are in agreement with a previous report, in that by screening the steatogenic potential of 76 different nuclear receptor ligands, 18% of the examined ligands, including RIF, exhibited enhanced lipid accumulation in human liver cells (Moya et al, 2010). On the other hand, ketoconazole, an established inhibitor of PXR, improved the metabolic function of high-fat diet-fed mice (Huang et al, 2007;He et al, 2013). Although activation of PXR may influence the expression of multiple genes associated with lipid metabolism such as CD36, stearoyl CoA desaturase 1, and long-chain fatty acid elongase, identification of SLC13A5 as a novel target gene of PXR further highlights the multifaceted role of this receptor in energy homeostasis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in agreement with a previous report, in that by screening the steatogenic potential of 76 different nuclear receptor ligands, 18% of the examined ligands, including RIF, exhibited enhanced lipid accumulation in human liver cells (Moya et al, 2010). On the other hand, ketoconazole, an established inhibitor of PXR, improved the metabolic function of high-fat diet-fed mice (Huang et al, 2007;He et al, 2013). Although activation of PXR may influence the expression of multiple genes associated with lipid metabolism such as CD36, stearoyl CoA desaturase 1, and long-chain fatty acid elongase, identification of SLC13A5 as a novel target gene of PXR further highlights the multifaceted role of this receptor in energy homeostasis.…”
Section: Discussionsupporting
confidence: 82%
“…In cultured mouse primary hepatocytes, activation of PXR by either ligand binding or post-translational modification resulted in significant lipid accumulation Staudinger et al, 2011). On the other hand, ablation of PXR alleviates high-fat diet-induced obesity, hepatic steatosis, and insulin resistance in mice (Biswas et al, 2009;He et al, 2013). Collectively, these results suggest that activation of PXR may not only influence genes involving xenobiotic metabolism/ detoxification, but also functions as a metabolic sensor affecting energy metabolism associated with various metabolic disorders.…”
Section: Introductionmentioning
confidence: 70%
“…PXR-apoE double knockout mice have a reduced atherosclerotic burden [41,42] and PXR-ob/ob mice or PXR knockouts on a high-fat diet show increased obesity and insulin resistance [43]. A strong note of caution must however be made when interpreting the PXR knockout mouse, as distinct functional differences are found between murine and human PXR in the humanized-PXR mouse and in animal models where pharmacological drug responses have been observed.…”
Section: Xenobiotic Receptorsmentioning
confidence: 99%
“…Another report showed that acute activation of PXR increased plasma triglyceride levels in both LDL receptor-deficient and ApoE-deficient (ApoE 2/2 ) mice but decreased LDL cholesterol levels in LDL receptor-deficient mice ). Activation of PXR can regulate many genes involved in lipid homeostasis including CD36, stearoyl-CoA desaturase-1,7-dehydrocholesterol reductase, S14, and lipin-1 in the liver, intestine, or macrophages of several animal models (Zhou et al, 2006b(Zhou et al, , 2009bde Haan et al, 2009;Hoekstra et al, 2009;Moreau et al, 2009;Cheng et al, 2012;He et al, 2013). These studies indicate that PXR can mediate cholesterol and lipid homeostasis at multiple levels.…”
Section: Introductionmentioning
confidence: 99%